Sustainable cellulose nanomaterials for environmental remediation - Achieving clean air, water, and energy: A review. (1st June 2022) - Wang, Qianqian; Liu, Simeng; Liu, Jun; Sun, Jianzhong; Zhang, Zhen; Zhu, Qianqian
Abstract: Environmental pollution is increasingly becoming a serious global challenge due to various pollutants. Cellulose nanomaterials (CNMs) based membranes originated from green resources and sustainable processes are expected to have great potential in environmental applications due to their nanoscale dimension, high surface area, biodegradability, and biocompatibility as well as renewable capability. To fully unlock this potential, fundamental understandings of the interplay between various tunable parameters of CNMs and the substances to be separated, are required for the rational design and fabrication of CNMs based membranes. This review highlights the recent advances in CNMs membranes for environmental remediation in achieving clean air, water, and green energy. Key parameters that dominate the performances of CNMs membranes are critically assessed. The interactions of CNMs with pollutants, molecules, and ions are analyzed and their selective transport mechanisms in different membrane separation processes are discussed. The challenges and future directions for CNMs membranes are also outlined. Graphical abstract: Unlabelled Image Highlights: Recent advances in CNMs membranes for environmental remediation are reviewed. The versatile applications of CNMs membranes for clean air, water, and energy are highlighted. The challenges and future directions for CNMs membranes are outlined.